Letter from Max Bredig to Georg Bredig and Marianne Homburger, March 1, 1936 - Bredig, Max Albert (1936)
Max Albert Bredig (1902-1977) writes to his father, Georg Bredig (1868-1944) and sister, Marianne Homburger née Bredig (1903-1986) to describe the work he is doing in Berlin. Max is studying how carbide phases can be converted by adding or removing calcium. He tells his father how he is struggling to find work. Finally, Max tells his father that he attended a Seder dinner, perhaps his first.
Keywords: Bredig, Max Albert, 1902-1977; Bredig, Georg, 1868-1944; Third Reich; Chemists; Chemistry; Homburger, Marianne, 1903-1986